PERFORMANCE OF DIFFERENT FERMENTATION METHODS AND THE EFFECT ON COFFEE QUALITY (Coffea arabica L.) - Peñuela-Martínez, Aida Esther; Zapata-Zapata, Arley David; Durango-Restrepo, Diego Luis (Coffee Science - ISSN 1984-3909, 2018)
Fermentation of coffee mucilage is a spontaneous process caused by microorganisms growing in the environment, which is influenced by factors such as the variety, climate and fruit maturity. These external factors play an important role in fermentation evolution because they have effect on the microorganism activity and the substrate transformation time. The objective in this research was to evaluate the effect of different fermentation wet process and evaluated their effect on coffee quality (Coffea arabica L.), as well as on organic acid concentrations and volatile organic compounds content, in the green coffee beans. The study was divided in two phases, one in which the pulping time was delayed and the fermentation methods were modified, and the second phase in which a bioreactor was used to control the pH and temperature of the coffee mass during fermentation. Two control treatments were used: without fermentation (mechanical removal of mucilage) and the traditional fermentation done in the farm. Significant differences in coffee quality were observed. The best quality was obtained from the treatments that used short process times and low temperatures. The concentrations of acetic, lactic and citric acids between the treatments and the control treatments were different. Higher contents of esters and ketones were found in the coffee that obtained the highest quality. The assessed processes lead to the conclusions that it is possible to improve coffee quality throughout introducing changes in the fermentation process, as well as modulating the acidity and fragrance of the final product.